2019
DOI: 10.1177/1474515119864759
|View full text |Cite
|
Sign up to set email alerts
|

The multiple mediating effects of illness perceptions and coping strategies on the relationship between physical symptoms and depressive symptoms in patients with heart failure

Abstract: Background: Depressive symptoms are prevalent and cause poor health outcomes in patients with heart failure. Studies show that the physical symptoms of heart failure are associated with depressive symptoms. However, little is known about the underlying mechanisms of this relationship. Aims: The purpose of our study was to examine the associations between physical symptoms, illness perceptions, coping strategies and depressive symptoms and to test the multiple mediation effects of illness perceptions and coping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 39 publications
6
21
2
1
Order By: Relevance
“…The mean HFSPS score in this study was higher than similar studies in the United States and Italy, along with another study that used this scale for a different purpose in China [12,31,[33][34][35]. In addition, the HFSPS was used to examine patients' physical symptoms in China as well [31]. However, a detailed analysis of subscale items was not discussed.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The mean HFSPS score in this study was higher than similar studies in the United States and Italy, along with another study that used this scale for a different purpose in China [12,31,[33][34][35]. In addition, the HFSPS was used to examine patients' physical symptoms in China as well [31]. However, a detailed analysis of subscale items was not discussed.…”
Section: Discussioncontrasting
confidence: 63%
“…In addition to the total score, which has good reliability (Cronbach's α: 0.90), a six-item dyspnea subscale, and seven-item early and subtle subscale were significantly associated with 1-year event-risk [29]. Psychometrics for the Chinese version of the HFSPS was 0.87 [31]. In this sample, the Cronbach's α was 0.690.…”
Section: Variables and Instrumentsmentioning
confidence: 79%
“…What is found is that in the case of the present study, the question about diseases was broad (presence/absence), so it was ascribed to the subjectivity of the patient to consider whether he/ she had a physical disease. It could be hypothesized that having more depressive symptoms makes subjects more receptive to feeling "sick," so it is important that in the future this measure can specify what type of disease is afflicting the patient and as refers Chen et al (2020) the illness perception of the patient. Depression and medical illness can be explained in several ways, for example, people suffering for a medical issue may have limitations in their daily life (e.g., pain, diabetes, cefalea, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study showed that depressive symptoms were significantly associated with maladaptive coping in older veterans with HF [11]. Depressive symptoms were positively correlated with acceptance-resignation coping in HF patients [12]. The results of preliminary study in one of hospital in East Java, Indonesia, showed that patients who experienced high levels of anxiety had partially maladaptive coping.…”
Section: Introductionmentioning
confidence: 93%